Urinary screening for early detection of kidney disorders in asymptomatic Indonesian adolescents - Ferry Liwang; Reza Fahlevi; Henny Puspitasari; Eka Hidayati; Sudung Pardede; Pringgodigdo Nugroho (Paediatrica Indonesiana, 2026)
Background Chronic kidney disease (CKD) in children, with global incidence ranging from 15–74.7 cases per million, can lead to lifelong sequelae and impose a significant healthcare burden. In Indonesia, Survei Kesehatan Indonesia 2023 showed that among individuals aged 15–24 years, 0.02% had CKD, and 16.2% of those with CKD underwent hemodialysis. Given that the early stages are frequently asymptomatic, urinary screening provides a simple, non-invasive method for early detection and prevention of future deterioration in kidney function. Objective To measure the prevalence of abnormal urinary findings in healthy, asymptomatic Indonesian adolescents aged 12–18 years using dipstick testing and microscopic urinalysis. Methods Over a 2-year period (2023–2024), we screened healthy, asymptomatic adolescents aged 12–18 years using spot (non–first-morning) urine specimens. Urine dipstick and microscopic tests were performed. Data collected included clinical characteristics and urine findings. Abnormalities such as isolated proteinuria, hematuria, leukocyte esterase, nitrite, and crystals were analyzed. Results Among 406 subjects (55.9% male; median age 15.67 years), 17% had isolated proteinuria, 14.3% had isolated hematuria, and 5.9% had both. Microscopic analysis revealed erythrocytes ≥3/hpf in 3.4% of subjects, and proteinuria +3 in 0.5% of subjects. Leukocyte esterase and nitrite were positive in 10.6% and 1.2% of subjects, respectively, though only 18.6% of leukocyte esterase–positive cases had leukocyte sediment >5/hpf. Abnormal crystals were found in 29.6% of cases, mainly associated with high urine specific gravity or urate crystals. Conclusion Proteinuria and hematuria, markers of early kidney damage, are detectable in asymptomatic adolescents. Routine urinary screening should be considered for Indonesian adolescents to facilitate early diagnosis and intervention.